Penerapan IPTEKS Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah di Kelurahan Koya Barat Distrik Muara Tami Kota Jayapura - Rongalaha, Johan; Palenewen, James Yoseph; Tanati, Daniel; Reumi, Frans; Pelupessy, Eddy; Solossa, Marthinus; Ketaren, Dahliana; Mamoribo, Margaretha G.M.I; Pondayar, Yustus; Wospakrik, Decky D. A. (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service is carried out with the title Implementation of IPTEKS Government Regulation Number 24 of 1997 Concerning Land Registration in Koya Barat Village, Muara Tami District, Jayapura City, which was carried out in Koya Barat Village, which was carried out to partners because of cases from partners regarding their lack of understanding of land registration and land registration procedures so that with the expertise possessed by the community service personnel, they can implement the IPTEKS. The method of implementing this community service is carried out by means of lectures and discussions which were held on Friday, July 26, 2024 which were held at the Koya Barat Village Office and providing assistance to partners which has been carried out until now, this activity begins with preparation and coordination, then presentation of material on the land registration process based on laws and regulations to obtain legal certainty. The output of this community service is the increase in partner knowledge regarding land registration and land registration procedures in order to obtain legal certainty, and also the completeness of land registration as a pre-adjudication with the aim of making it easier for partners to complete land registration.